2-Quinolylmethyl N0-[1-(m-tolyl) ethylidene] hydrazinecarbodithioate - How, Fiona Ni Foong; Watkin, David J.; Crouse, Karen Anne; Mohamed Tahir, Mohamed Ibrahim (International Union of Crystallography, 2007)
The title compound, C20H19N3S2, crystallized as a cis–trans conformer in which the quinoline ring system is cis across the C—S bond but adopts a trans geometry with respect to the C—N bond. The compound exists in the thione form with the presence of a C S bond.